CMOS Neural Probe With 1600 Close-Packed Recording Sites and 32 Analog Output Channels - Sayed Herbawi, Abdalrahman; Christ, Olaf; Kiessner, Lukas; Mottaghi, Soheil; Hofmann, Ulrich G.; Paul, Oliver; Ruther, Patrick (Journal of microelectromechanical systems, 2018)
This paper reports on the development, characterization, and validation of neural probes serving the growing needs of neuroscience for miniaturized tools enabling simultaneous high-resolution recording of neural activity in multiple brain areas. The probes consist of a needle-shaped shaft with a cross-section of 100× 50\,μ \text{m}^{2} and a length of 10 or 5 mm emerging from a base with dimensions of only 0.55× 1.8 mm 2 . The shafts carry 1600 and 800 recording sites, respectively, grouped into 50 (respectively 25) blocks of 4× 8 electrodes with an area of 17× 17\,μ \text{m}^{2} each, a pitch of 20 μ \text{m} , and an electrode-to-electrode spacing of 3 μ \text{m} . The probes are fabricated using a commercial 0.18 μ \text{m} CMOS process followed by dedicated metallization, passivation, and microfabrication steps. Neural signals are accessible through 32 analog output channels via a hierarchical digital addressing scheme implementing an advanced electronic depth control concept giving the option of multiple scanning modes and offering a switching time of 416 μ \text{s} at a clock frequency of 1 MHz. All output channels are shielded against each other, whereby crosstalk between neighboring channels is measured to be −58 dB at 1 kHz. Absolute impedance values at 1 kHz of single IrO x and Pt electrodes are 230± 38~\text{k}Ω and 2.2± 0.3~\text{M}Ω , respectively. In vivo recordings taking advantage of the new addressing concept for high-resolution recordings from multiple brain regions were successfully performed in anesthetized rats. [2018-0152]